2021
DOI: 10.1177/14651165211040337
|View full text |Cite
|
Sign up to set email alerts
|

Issues that mobilize Europe. The role of key policy issues for voter turnout in the 2019 European Parliament election

Abstract: In light of the unexpectedly high turnout in the 2019 European Parliament election, we explore how major transnational policy issues mobilize voters in European electoral contests. Based on the analysis of two data sets, the Eurobarometer post-election survey and the RECONNECT panel survey, we make three important observations. First, European citizens show a higher tendency to participate in European Parliament elections when they attribute greater importance to the issues ‘climate change and environment’, ‘e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…As policy issues related to the economy, migration and climate change will continue to dominate European politics in the future, the implications for representation, accountability and responsiveness remain imperative to study. These issues are likely to mobilize the European electorate in future European and national elections as the findings of Braun and Schäfer (2022) suggest citizens of the EU will look at Britain as a 'benchmark' of how a country might develop outside the EU (Hobolt et al, 2022). On the one hand, the Brexit negotiations were chaotic and the British economy will be affected negatively, making the prospects of countries leaving the EU less appealing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As policy issues related to the economy, migration and climate change will continue to dominate European politics in the future, the implications for representation, accountability and responsiveness remain imperative to study. These issues are likely to mobilize the European electorate in future European and national elections as the findings of Braun and Schäfer (2022) suggest citizens of the EU will look at Britain as a 'benchmark' of how a country might develop outside the EU (Hobolt et al, 2022). On the one hand, the Brexit negotiations were chaotic and the British economy will be affected negatively, making the prospects of countries leaving the EU less appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Braun and Schäfer (2022) in their contribution to this special issue address precisely that question. They argue that individuals who regard certain policy issues, such as climate change and environment, economy and growth, as well as immigration, as one of the most important problems to solve, are also more likely to take part in EP elections.…”
Section: Consequences For Eu Electoral Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these events had high levels of visibility and resulted in controversy for a European project that, as discussed above, was thitherto based on "permissive consensus" (De-Wilde; Laupold; Schmidtke, 2016). The presence of EU issues has led to a politicization related to the EU (Risse, 2015), to the point that some issues such as climate change, the economy, or immigration can act as fissures that influence voting in European elections Schäfer, 2021).…”
Section: The Rise Of Euroscepticism In a Multilevel Europementioning
confidence: 99%
“…The fight against climate change has become a pressing issue on the agenda of the European Union (EU). The 2019 European elections demonstrated that EU citizens considered climate change to be a major challenge for the Union, which translated into a much higher share of votes for green parties and the adoption of a European "Green Deal" as a major goal of the new Commission's work programme (Braun & Schäfer, 2022). After a period in which climate and environmental issues had been relegated to the bottom of the agenda (Burns, 2019), the start of the ninth legislative period (2019-2024) offered the European Parliament (EP) a renewed opportunity to push for more ambitious policy goals.…”
Section: Introductionmentioning
confidence: 99%